2016
DOI: 10.1186/s13048-016-0291-2
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian thecoma-fibroma groups: clinical and sonographic features with pathological comparison

Abstract: BackgroundOvarian thecoma-fibroma groups (OTFG) are uncommon sex cord-stromal neoplasms. The objective of the study was to demonstrate clinical and sonographic features of OTFG and compare with surgical histopathology.MethodsA total of 61 patients with surgically proven OTFG were enrolled in this retrospective study to demonstrate its clinical and sonographic features and to compare with pathological findings. Gray scale and color Doppler sonography were performed presurgically with either transabdominal or tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 22 publications
5
44
0
Order By: Relevance
“…Chen et al report that 63.93% of the lesions occur after menopause, with 65.57% in women aged 51 to 70 years. Most patients visited the hospital because of pelvic palpable masses, while 64% of these patients showed no obvious clinical symptoms [5,6]. Symptoms such as abdominal pain and abdominal bulging may occur in cases with large tumors with a diameter over 5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al report that 63.93% of the lesions occur after menopause, with 65.57% in women aged 51 to 70 years. Most patients visited the hospital because of pelvic palpable masses, while 64% of these patients showed no obvious clinical symptoms [5,6]. Symptoms such as abdominal pain and abdominal bulging may occur in cases with large tumors with a diameter over 5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian fibroma/fibrothecoma with elevated serum CA125 level is rarely encountered in clinical practice, and can be indexed in only 2 studies with small samples. [ 2 , 3 ] Chechia et al [ 3 ] measured serum CA125 level in 21 fibroma/fibrothecoma patients and found that 3 (14.2%) had values ≥ 35 U/mL. Chen et al [ 2 ] found that 12 (20.6%) had serum CA125 value ≥ 35 U/mL in 58 ovarian fibroma/fibrothecoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian fibroma/fibrothecoma is classified as sex cord stromal tumors, accounting for approximately 5% to 8% of all ovarian tumors and including 3 pathologic subtypes (fibroma, thecoma, and fibrothecoma) based on the different compositions of fiber and theca ingredients. [ 2 ] Most of ovarian fibromas/fibrothecomas occur in adolescents and young women, and show a solid pelvic or adnexal mass with benign biobehavior. About 10% to 15% of ovarian fibromas/fibrothecomas can be combined with ascites, however, less than 1% are combined with both ascites and hydrothorax, known as Meigs syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…They are often unilateral with a diameter smaller than 5 cm. Combined with clinical information and CA125, ultrasound imaging could be used as an imaging tool for improving the preoperative diagnostic accuracy [5]. It has been reported that 34% of ovarian fibromas were misdiagnosed preoperatively as uterine myoma [4].…”
Section: Discussionmentioning
confidence: 99%